Eksistensi Perjanjian Pra Nikah Dalam Persfektif Hukum Islam Indonesia - Pratama, Widhy Andrian (LPPM IAIN Sorong, 2025)
The background of this Prenuptial Agreement is to not deviate from the provisions of statutory law, which regulates that the personal wealth of each husband and wife is basically mixed into one whole. Another reason that is the background of the holding of the Prenuptial Agreement is if there is a striking difference in social status between the prospective husband and wife, or they have equal personal wealth, or the giver of the gift does not want something given to one of the husband and wife to transfer to another party, or each husband and wife are subject to different laws as is the case in mixed marriages. The author uses a data approach in this study through library research, with data collection techniques that involve searching for relevant documents, such as journals, books, articles, and other materials. In addition, information from electronic and print media related to the topic discussed is also used as part of the data source. Prenuptial agreements play an important role in creating legal certainty, protecting personal wealth, preventing potential disputes, and preparing couples both emotionally and legally before marriage. However, the preparation of this agreement must be done with good intentions and in accordance with the regulations in force in Indonesian Marriage Law. Although prenuptial agreements provide significant benefits in maintaining family harmony and well-being, their implementation still faces various challenges, especially in ensuring compliance with applicable laws and maintaining a balance of rights and obligations for both parties.